A prospective study on the effect of ethambutol on retinal nerve fiber layer thickness and central macular thickness - Sanchari Sarkar; Sanjay Kumar Daulat Thakur; Aparup Dhua; Avik Dey Sarkar; Payel Khatua (Journal of Clinical Ophthalmology and Research)
Background: Ethambutol-induced optic neuropathy is a sight-threatening side effect seen in patients receiving antitubercular drugs. The prevalence is estimated to be about 1%–2%. Objective: The objective of the study was to assess the effect of ethambutol (EMB) on retinal nerve fiber layer (RNFL) Thickness and central macular thickness (CMT) in patients of newly diagnosed pulmonary tuberculosis. Methods: Forty-four eyes of 22 patients were studied for alteration in quadrant-wise RNFL thickness and CMT post-initiation of EMB. RNFL thickness and CMT measurement by spectral domain-optical coherence tomography were done at baseline and as well as after 2 and 4 months of treatment, respectively. Results: RNFL thickness decreased significantly in all quadrants (P < 0.01) and CMT increased significantly (P = 0.02) at the end of 4 months compared to baseline. While RNFL thinning in the nasal quadrant was significant throughout (P < 0.001), it was significant for the remaining three quadrants only in the intensive phase (P < 0.001, P = 0.018, and P < 0.001). Conclusion: EMB leads to RNFL thinning and an increase in CMT, even in patients with normal best-corrected visual acuity. Hence, EMB should be administered cautiously in patients presenting with RNFL thinning at baseline or with macular disorder with an increased propensity for retinal thickening.